The influence of nitrogen fertilization, physiological stage and season on qualitative and quantitative characteristics of Panicum maximum cv Gatton for sheep - Van Niekerk, Willem A. (University of Pretoria, 2013)
Dissertation (MSc Agric (Animal Nutrition))--University of Pretoria, 2006.